1987
DOI: 10.1007/bf00215747
|View full text |Cite
|
Sign up to set email alerts
|

Transport of membrane-bound macromolecules by M cells in follicle-associated epithelium of rabbit Peyer's patch

Abstract: M cells in Peyer's patch epithelium conduct transepithelial transport of luminal antigens to cells of the mucosal immune system. To determine the distribution of specific lectin-binding sites on luminal membranes of living M cells and to follow the transport route of membrane-bound molecules, lectin-ferritin conjugates and cationized ferritin were applied to rabbit Peyer's patch mucosa in vivo and in vitro. The degree to which binding enhances transport was estimated by comparing quantitatively the transport o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0
3

Year Published

1988
1988
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(131 citation statements)
references
References 31 publications
2
126
0
3
Order By: Relevance
“…Although the reason for this finding remains unclear, it is well established that M cells in the gut can transport intact macromolecules across epithelial barriers (27,28). Thus, it is theoretically possible under such a scenario that oral intake of pork could lead to an interaction of M cell-associated, gut-infiltrating lymphocytes with directly presented SLA molecules to prime an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reason for this finding remains unclear, it is well established that M cells in the gut can transport intact macromolecules across epithelial barriers (27,28). Thus, it is theoretically possible under such a scenario that oral intake of pork could lead to an interaction of M cell-associated, gut-infiltrating lymphocytes with directly presented SLA molecules to prime an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Large particles and bacteria induce phagocytosis that is associated with rearrangement of the actin cytoskeleton and this permits active formation of pseudopod-like structures [15,33]. Viruses and adherent particles are taken up by endocytosis, but non-adherent materials are internalized by fluid phase endocytosis [14,74,81]. We are a long way from understanding the origin, differentiation, and fate of FAE in ileal PP.…”
Section: Follicle-associated Epithelium and Other Accessory Cells Of mentioning
confidence: 99%
“…Although further studies are required to understand the mechanism, M cells are plausible targets for the orally administered mucus containing the lectin and TLPs. M cells express particular glycosylation patterns on their surfaces and transport a wide range of molecules from the intestinal lumen to the underlying lymphoid tissue, where a local and systemic potent immune response is initiated (Neutra et al, 1987). It has been reported that some plant lectins are able to induce T helper cell type 1 (Th1) cytokines upon interaction with glycosylated receptors on macrophages and/or dendritic cells, such as type 2 and 4 Tolllike receptors (TLR2 and TLR4), respectively (Souza et al, 2013).…”
Section: Discussionmentioning
confidence: 99%